2014
DOI: 10.2337/db13-0468
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiac Arrhythmias During Hypoglycemia in Patients With Type 2 Diabetes and Cardiovascular Risk

Abstract: Recent trials of intensive glycemic control suggest a possible link between hypoglycemia and excess cardiovascular mortality in patients with type 2 diabetes. Hypoglycemia might cause arrhythmias through effects on cardiac repolarization and changes in cardiac autonomic activity. Our aim was to study the risk of arrhythmias during spontaneous hypoglycemia in type 2 diabetic patients with cardiovascular risk. Twenty-five insulin-treated patients with type 2 diabetes and a history of cardiovascular disease or tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
254
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(287 citation statements)
references
References 43 publications
(44 reference statements)
18
254
1
14
Order By: Relevance
“…In studies using continuous glucose and cardiac monitoring devices, hypoglycemia was associated with an increase in arrhythmias and prolonged QT intervals (75). Enhanced sympathetic nervous system activation, catecholamine excess, and abnormal cardiac repolarization observed with hypoglycemia can potentially contribute to ASCVD risk and events (85,86).…”
Section: Hypoglycemia As a Cardiovascular Risk Factormentioning
confidence: 99%
“…In studies using continuous glucose and cardiac monitoring devices, hypoglycemia was associated with an increase in arrhythmias and prolonged QT intervals (75). Enhanced sympathetic nervous system activation, catecholamine excess, and abnormal cardiac repolarization observed with hypoglycemia can potentially contribute to ASCVD risk and events (85,86).…”
Section: Hypoglycemia As a Cardiovascular Risk Factormentioning
confidence: 99%
“…The reasons for failure of the HbA 1c -based glycemic control strategies used in these more recent studies are not clear, but one possibility is that HbA 1c levels do not assess variability in plasma glucose levels; that is, HbA 1c does not directly reflect the frequency or severity of either hypoglycemic events or hyperglycemic increments after meals, both of which may cause physiologic changes that contribute to long-term risks. Possible mechanisms for such effects include systemic inflammation (8,9), oxidative stress (10), endothelial dysfunction (11,12), intimal-medial thickening (13), and cardiac ischemia or arrhythmias (14)(15)(16). Considerable literature linking various CVD risk markers with glycemic variability has been published (17,18).…”
mentioning
confidence: 99%
“…The obvious question of whether the relationship between severe hypoglycaemia and mortality is causal or mere association remains undetermined [5]. Although experimental studies in humans and rodents have identified potential mechanistic changes that could explain an association, for example, by inducing cardiac dysrhythmias [6,7], infrequent fatal events are difficult to study at a population level. However, whether it increases the risk of dying or not, hypoglycaemia is still clinically important, being feared by patients as much as chronic complications, increasing the risk of accidents, carrying social and economic costs (e.g.…”
Section: Accord Action To Control Cardiovascular Risk In Diabetesmentioning
confidence: 99%